Comparison of outcomes with the single‐puncture and double‐puncture techniques of arthrocentesis of the temporomandibular joint: An updated systematic review and meta‐analysis. (23rd July 2021) - Nagori, Shakil Ahmed; Bansal, Adity; Jose, Anson; Roychoudhury, Ajoy
Abstract: Objective: To compare intra‐operative and postoperative outcomes between the single‐puncture and the standard double‐puncture techniques of arthrocentesis. Methods: PubMed, Embase, ScienceDirect and CENTRAL databases were searched from inception up to 31 st August 2020. Randomised controlled trials (RCTs), prospective and retrospective studies conducted on patients with temporomandibular joint disorders comparing any type of single‐puncture arthrocentesis with standard double‐puncture arthrocentesis and reporting intra‐operative/postoperative outcomes were included. Assessment of the risk of bias was done with the Cochrane Collaboration risk assessment tool. Results: Thirteen studies were included (12 were RCTs). Analysis of a limited number of studies indicated no difference in pain or maximal mouth opening (MMO) between the single‐puncture type‐1 or type‐2 and the double‐puncture technique at various follow‐up intervals. Pooled analysis (four studies) demonstrated that the single‐puncture type‐2 technique requires significantly less operating time as compared to the double‐puncture method. No such difference was noted between single‐puncture type‐1 and double‐puncture techniques. Analysis of two studies indicated significantly reduced intra‐operative needle relocations with the single‐puncture techniques. Studies were not of high quality with concerns of bias in randomisation, allocation concealment and blinding. Conclusions: Limited data indicate no difference in pain or MMO with single‐ or double‐puncture techniques of arthrocentesis. Amongst the three techniques, the single‐puncture type‐2 technique has the advantages of significantly lower operating time and reduced intra‐operative needle relocations and it may be the preferred method of TMJ arthrocentesis in clinical practice. Abstract : Our review is a pooled analysis of 13 studies comparing single puncture and double puncture techniques of arthrocentesis. Meta‐analysis indicates no difference in pain or maximal mouth opening with single or double puncture techniques of arthrocentesis. Amongst the three techniques, the single puncture type 2 technique has the advantages of significantly lower operating time and reduced intra‐operative needle relocations and it may be the preferred technique in clinical practice.